Humble Hopes in Mentorship and Education: Thinking with Temporality - Bente Ulla; Ann Sofi Larsen (MDPI AG, 2021)
This article juxtaposes mentoring with an extended concept of time, arguing against the idea of mentoring as a unilaterally forward-moving progression. We discuss how time and temporality unfold in mentoring in the teaching profession. We further explore how temporality might create different potentialities of hope. Ultimately, we suggest the necessity of destabilising narratives of mentoring as constant and linear improvements. We use an example of an inheritance from the past as an analogy in order to provide a thematic starting point for our discussion. This example supports the exploration of how mentorship programme assignments are experienced as well as how conversations are constantly filtered through time. The article builds on the empirical elements of a study of a mentorship programme to explore potentialities that are of importance in mentorship and education.